Pendidikan Rohani Dalam Tradisi Amaliyah Di Pondok Pesantren Salafiyah Kota Kediri - Farah Al Kiftiyah; A. Jauhar Fuad (Indonesian Journal of Humanities and Social Sciences, 2020)
In this study, the authors used a descriptive qualitative approach which departed from two questions, namely; 1.) "What is Amaliyah doing at the Salafiyah Islamic Boarding School in Kediri?", 2.) How is the relationship between Amaliyah at the Salafiyah Islamic Boarding School and spiritual education? " With these several questions, the results of the research conducted found that spiritual education in the amaliyah tradition at the Salafiyah Islamic Boarding School includes: grave pilgrimages, prayer beads, and recitation of 1000 sholawat. With this amaliyah tradition, we are able to; 1.) overcoming anxiety, fear, and uneasiness of the hearts of the students, 2.) calming the soul, because in it there are things that bring calm, such as dzikrullah in reading tahlil, tahmid, tasbih, and sholawat., 3.) giving direction, motivation and finally grow full awareness to obey, submit to carry out orders and know the prohibitions.